2023
DOI: 10.1007/s10488-023-01250-5
|View full text |Cite
|
Sign up to set email alerts
|

Unintentional Discrimination Against Patients with a Migration Background by General Practitioners in Mental Health Management: An Experimental Study

Abstract: Populations with a migration background have a higher prevalence of mental health problems than their native counterparts. They are also more likely to have unmet medical needs and are less frequently referred to mental health services. One potential explanation for this is that physicians, such as general practitioners (GPs), may unintentionally discriminate against migrant patients, particularly when they lack humanization. To date, no experimental study has investigated this hypothesis. This paper assesses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In contrast, in the Netherlands there is a high rate of referral and non-medical mental health care use. For individuals from non-neighboring countries, this may be due to their underrepresentation in ambulatory health care, which could be caused by cultural-specific barriers such as language barriers or differences in preferences and health care seeking behavior (62)(63)(64). Barriers can also occur at the level of health care providers, where patients from non-neighboring countries are treated differently, which is described as provider bias (65, 66).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the Netherlands there is a high rate of referral and non-medical mental health care use. For individuals from non-neighboring countries, this may be due to their underrepresentation in ambulatory health care, which could be caused by cultural-specific barriers such as language barriers or differences in preferences and health care seeking behavior (62)(63)(64). Barriers can also occur at the level of health care providers, where patients from non-neighboring countries are treated differently, which is described as provider bias (65, 66).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, it can be debated if these GPs have sufficient knowledge on potential cultural influences to diagnose and refer migrant patients. Research has provided evidence that GPs may make suboptimal diagnostic, treatment, and referral decisions with migrant patients (Centola et al 2021;Duveau et al 2023). Amongst other reasons such as language barriers, this was also due to the influence of practitioners' behaviours and beliefs on their decisionmaking process.…”
Section: Specific Mental Healthcare Initiatives For Migrants In Belgium?mentioning
confidence: 99%
“…Amongst other reasons such as language barriers, this was also due to the influence of practitioners' behaviours and beliefs on their decisionmaking process. In specific Belgian studies (Delaruelle et al 2022;Duveau et al 2023;Lepièce et al 2014), it was found that Belgian GPs displayed less favourable and discriminatory decision-making regarding mental health for migrant patients. GPs (unintentionally) perceived the symptoms of migrant patients as less severe compared to those of native patients, dedicated less time to examine the sociorelational history of their migrant patients, and prescribed more drugs.…”
Section: Specific Mental Healthcare Initiatives For Migrants In Belgium?mentioning
confidence: 99%